The use of kahoot platform to encourage vocabulary in english. - Cuenca Azuero, Wilmer Israel (Machala : Universidad Técnica de Machala, 2021)
The main objective of this research is to improve the teaching of English vocabulary with second-level students at the Language Institute, through a system of didactic activities using the Kahoot platform for the improvement of English vocabulary. The research responds to a mixed paradigm, with a non-experimental, descriptive design, making use of theoretical methods that made it possible to systematize different existing criteria on the subject, facilitating a better approach to the work, while, with the help of empirical methods such as participant observation, diagnostic test, and the teacher survey, they made it possible to diagnose the initial and final state of the study population made up of second-level students. The intervention proposal to a system of didactic activities that favours both teaching and learning in the students was planned for a unit of study. Finally, it is recommended that future teachers make use of new technological tools focused on all types of students.
Esta investigación tiene como principal objetivo mejorar la enseñanza del vocabulario en inglés con los estudiantes de segundo nivel del Instituto de idiomas, a través de un sistema de actividades didácticas en la utilización de la plataforma Kahoot para la mejorara del vocabulario en inglés. La investigación responde a un paradigma mixto, con un diseño no experimental, de tipo descriptivo, haciendo uso de métodos teóricos que permitieron sistematizar distintos criterios existentes sobre la temática, facilitando un mejor abordaje del trabajo, mientras que, con la ayuda de los métodos empíricos como la observación participante, test de diagnóstico, y la encuesta a la docente, permitieron diagnosticar el estado inicial y final de la población en estudio conformado por los estudiantes de segundo nivel. La propuesta de intervención a un sistema de actividades didácticas que favorece tanto la enseñanza como el aprendizaje en los estudiantes y que fue planificada para una unidad de estudio. Finalmente se recomienda que los futuros docentes hagan uso de nuevas herramientas tecnológicas centrado a todo tipo de estudiantes.
Keywords: ACTIVITY SYSTEM; KAHOOT PLATFORM; VOCABULARY; LEARNING PROCESS